18Popular Culture. (3rd October 2019) - Potts, Tracey
Abstract: This year's chapter explores themes of consumption, popular culture, and sustainability in publications from 2018. Starting with the biggest issue we face today—climate change—the aim is to survey and complicate the picture of the consumer and consumer culture by way of refusing some of the more glib accounts of over-consumption. The heavy lifting of the discussion is accomplished by an article that dissects recent scholarship around consumer practice and the environment. This article then forms a framework for looking at books on souvenirs, pop music heritage, digital music, and American popular culture, ending with a sustained look at the cultural anatomy of the hamburger.